ANALISIS PERBANDINGAN PENERIMAAN PPN &PPn BM SEBELUM DAN SESUDAH PENERAPAN METODE E-FILING PADA KPP PRATAMA SERANG - Iroh Rahmawati (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2020)
From an economic point of view, taxes are state revenues used to direct people's lives towards prosperity. Tax as a driving force for people's economic life. By applying the e-filling method in the PPN & PPn BM tax service system, it is expected that state revenue can increase. The purpose of this study was to analyze the comparison of acceptance of PPN & PPn BM before and after the e-filling method was applied. Data analysis technique used paired test sample T-test with the help of SPSS. To find out whether or not the hypothesis was accepted, a comparison of tcount (-2,392) and t-table (2,201) was used. Based on calculations it is known that there was no significant difference in the amount of PPN & PPn BM receipts before and after the e-filling method was applied.